Perceived benefits of training, individual readiness for change, and affective organizational commitment among employees of national jordanian banks - Ayman Mansour; hefin Rowlands; Jassim Ahmad Al-Gasawneh; Nawras M. Nusairat; Shaker Al-Qudah; Hosam Shrouf; Abdel Hakim Akhorshaideh (Cogent Business & Management, 2022)
This study aimed to examine how employees' perceived benefits of training impact their level of affective organizational commitment through investigating the mediating role of individual readiness for change in National Jordanian banks. The study sample included 451 employees from 16 banks in Jordan. Stratified random sampling was used for the selection of the study participants, and data were collected using a self-administered written questionnaire. Partial least squares structural equation modelling was conducted to analyze the collected data and test the study hypotheses, which were developed according to the social exchange theory and psychological contract theory. The analysis provided strong evidence for the contentions of the social exchange theory, whereby employees' affective commitment to their banks was found to be positively influenced by their perceptions of the job-, career, and personal-related benefits of training. Moreover, individual readiness for change was shown to be positively influenced by employees' perceived benefits of training, and employees' affective organizational commitment was positively influenced by their readiness for change. Finally, individual readiness for change was found to act as a mediating variable between employees' perceived benefits of training and their level of affective commitment to their banks. The current study provides bank management teams with a comprehensive understanding of employees' affective organizational commitment as a potential outcome of training and provides evidence for the relationship between the two variables.
Keywords: 650; Jordan; Banks; Affective organizational commitment (AOC); Employees' perceived benefits of training (EPT); Individual readiness for change (IRFC)